DETECTION OF GENES RESISTANT TO BACTERIAL LEAF BLIGHT IN RICE CULTIVARS FROM SITUBONDO AND JEMBER, INDONESIA - .,, Rasmiyana; Addy, Hardian Susilo; Narulita, Erlia (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Detection of genes resistant to bacterial leaf blight in rice cultivars from Situbondo and Jember, Indonesia. Xanthomonas oryzae pv. oryzae (Xoo), causing bacterial leaf blight, is a destructive pathogen that significantly affects rice production. The use of resistant varieties is the most effective and economical strategy to reduce the impact of the disease. This study aimed to analyze the genetic basis of resistance to Xoo in rice. The incidence and severity of bacterial leaf blight were assessed in the field through a diagonal random sampling method. PCR was used to detect resistant genes in rice with eight Xa-specific primers. The presence of Xa genes and environmental conditions were statistically analyzed to determine whether the disease incidence and disease severity were related to average temperature and rain intensity. The means for disease incidence and severity at the generative stage were higher than those at the vegetative stage. The 12 rice cultivars were categorized into four groups based on the presence of Xa gene sequences; most cultivars had Xa10 and Xa13, and one cultivar had five Xa genes. Disease incidence and severity were weakly correlated to the presence of resistance genes, as well as to environmental factors. Most rice cultivars from the Regencies of Jember and Situbondo carry Xa10 and Xa13 resistance genes.